Position Paper from the Portuguese Association of Hospital Pharmacists for biosimilar therapeutic antibodies. (11th November 2016) - Goncalves, J.; Matos de Brito, P.; Batista, A.; Feio, J.; Machado, F.; Aperta, J.; Ascensão, I.; Pires, V.; Oliveira, C.; Armandina Pontes, R.; Alcobia, A.; Paulo Cruz, J.; et al.
Summary: What is known and Objective: Biopharmaceuticals are an important class of drugs for the treatment of autoimmune/inflammatory and oncologic diseases. With patent expiries, biotechnological manufacturers can now develop biosimilar drugs. Due to timeliness of introducing new and more complex biosimilars, the Portuguese Association of Hospital Pharmacists gathered to develop a common positioning on the use of biosimilar monoclonal antibodies. Main issues: The European pathway to biosimilar approval was developed to improve affordability and access to biological therapies, but it remains a work in progress because unresolved issues remain. Due to the present reality of biosimilar monoclonal antibodies, hospital pharmacists must play an important role in ensuring the safe, effective and cost‐effective use of biosimilars in health systems; and educating healthcare administrators, providers, legislators, policymakers, payors and patients about these products. What is new and conclusion: The conclusions presented in this work focused on the proposal for optimal biosimilar prescription criteria, the preparation of original biologics and biosimilars in the pharmacy, the management and selection of suppliers, extrapolation issues, the specific role of pharmacovigilance and risk management for the optimal use of biosimilar monoclonal antibodies. Abstract : This work focused on the proposal of optimal biosimilar prescription criteria, the preparation of original biologics and biosimilars in the pharmacy, the management and selection of suppliers, the specific role of pharmacovigilance and risk management for the optimal use of biosimilar monoclonal antibodies.